Assessing the functionality of sand dams as a dryland water source through an evaluation of water loss pathways - Ritchie, Hannah Nicola Grace (Cranfield University, 2024)
Between 1 - 2 billion people worldwide suffer from water scarcity, most of whom live in drylands. Irregular but intense rainfall have led to the proliferation of water harvesting. Sand dams, one such technique, comprise a concrete dam wall constructed across ephemeral rivers, which facilitate the accumulation of alluvium. Such dams can store and lose water to varying degrees, the extent of which is unclear. This research therefore aimed to evaluate spatial and temporal water losses from sand dams in order to understand their storage potential and their contribution to water availability within the river channel and surrounding weathered basement aquifer. Through monitoring telemetered abstraction data and employing analytical modelling, this thesis explored variations in rates of water use and seepage from sand dams in Kenya. By being the first study to use 2D geophysics at sand dams, it improved the understanding of how sand dams interact with the surrounding hydrogeological environment. Contrary to assumptions, geophysical inversions successfully showed that the trapped alluvium of sand dams typically overlies weathered basement material up to approximately 25 m in thickness, rather than impermeable bedrock. Alongside simulated flow rates, averaging 32.4 m³/day and empirical evidence, results highlight a partial recharge function performed by sand dams, primarily driven by lateral flow. Despite this, estimated groundwater volumes at full capacity, of up to 4,200 m³, were sufficient to meet community water needs throughout the dry seasons, in part due to recharge to the sand dams. This indicates the storage capabilities of the studied sites. By identifying site and hydrogeological characteristics that may result in lower levels of seepage from the dams, and greater recharge to the dams, the findings aim to enhance site selection and dam construction, enabling more sand dams to better meet storage requirements. This will contribute to facilitating the implementation and scaling-up of sand dams in areas where they are physically suitable and appropriate to the specific needs of a community.
Parker, Alison - Associate Supervisor
Keywords: Kenya; Arid-Semi Arid Land (ASAL); Alluvial aquifer; Water Harvesting; Managed Aquifer Recharge (MAR); Water Security; Nature Based Solution (NBS); Ephemeral River; Abstraction; Seepage; Evaporation; Telemetry; Geophysics; Electrical Resistivity Tomography (ERT); Modelling.